To conduct research on Preparatory Tillage, Nutrient Managements and Moisture Conservation Practices as Response on Yield, Effective Fresh and Dry Weight of Barley Cultivation under Water Stress Condition (International Journal of Food and Nutritional Sciences, 2021)
A field experiment were conducted for two consecutive rabi seasons during 2017-18 and 2018-19 at Faculty of Agricultural Sciences and Allied Industries, Rama University, Mandhana,Kanpur, U.P. 209217 on Gangatic alluvial soil having 7.6 pH, light textured soil with mediumsoil fertility.